Policy, politics, health and housing in the UK - Dorling, D (Policy Press, 2015)
We need to focus policy and political attention on the very recent changes to the patterns of ownership and wealth in housing in Britain which have occurred since the 2008 financial collapse. A small group of private landlords, less than 2% of the population, have taken advantage of the new circumstances to rapidly enrich themselves and return Britain to a time when a very large number of families with children relied on private renting to provide them with a home, now 1 in 4 of all English families with children. The possible implications for health, politics and policy are profound.